2022
DOI: 10.1055/s-0042-1742623
|View full text |Cite
|
Sign up to set email alerts
|

Liberação endoscópica do túnel cubital na neurite hansênica do nervo ulnar

Abstract: Resumo Objetivos Os objetivos deste estudo foram caracterizar melhor o papel da liberação endoscópica do túnel cubital na neurite hansênica e determinar se há melhora da dor, sensibilidade e força com esta técnica minimamente invasiva. Métodos Um total de 44 procedimentos endoscópicos para descompressão do nervo ulnar no cotovelo foram realizados em pacientes previamente diagnosticados com neurite por hanseníase. Os critérios de inclusão foram indicação cirúrgica para liberação do nervo uln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Previous studies have shown similar results to those found in the present review, supporting the hypothesis that drug treatment, in association with neurolysis, reduces pain and physical repercussions in the affected limbs 33,34 . In the present review, eight studies 7,13-17,20-22 evaluated the reduction of neuropathic pain after neurolysis, while four evaluated neurolysis in conjunction with corticosteroid treatment 13,17,18,20 .…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown similar results to those found in the present review, supporting the hypothesis that drug treatment, in association with neurolysis, reduces pain and physical repercussions in the affected limbs 33,34 . In the present review, eight studies 7,13-17,20-22 evaluated the reduction of neuropathic pain after neurolysis, while four evaluated neurolysis in conjunction with corticosteroid treatment 13,17,18,20 .…”
Section: Discussionsupporting
confidence: 91%